The Effect of Gender Diversity on Asymmetric Cost Behaviour Using Earnings Management as a Mediating Variable - Sakhil, Ali Dakhil; Bajuri, Norkhairul Hafiz; Ali, Shireen Tawfeeq; Hasan, Hussein Falah; Khalbas, Huda Nathim (Advances in Social Sciences Research Journal, 2025)
Examining how gender diversity affects asymmetric cost behaviour in non-financial firms is the goal of the current study. Its primary objective is to ascertain whether earnings management mediates the association between gender diversity and asymmetric cost behaviour. The data utilised in this study came from 455 firm-year observations from 35 non-financial sector businesses registered on the Iraqi Stock Exchange from 2010 to 2022. The study employed ordinary least squares (OLS). The results showed that asymmetric cost behaviour and earnings management are unaffected by gender diversity. On the other hand, the results show that earnings management is negatively associated with asymmetric cost behaviour. Thus, the study fills the gap in the literature, especially in developing countries.